Human dignity and the emergence of combating modern slavery in Brazil - Trevisam, Elisaide; Trevisam Braga, Julio (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2020)
In view of the guarantee and protection of human dignity and decent work, this research aims to present a reflection on the emergency character of the combat against modern slavery in Brazil through international and internal devices, which guarantee the person’s fundamental rights, for the state to become able to sustain the title of a Democratic State of Law. To achieve the expected ends, the methodology used will be documentary and exploratory, using the deductive method, with bibliographic and documental character to evaluate the premises established in the research